The Role of MIF and IL-10 as Molecular Yin-Yang in the Modulation of the Host Immune Microenvironment During Infections: African Trypanosome Infections as a Paradigm - Stijlemans, Benoit; Schoovaerts, Maxime; De Baetselier, Patrick; Magez, Stefan; De Trez, Carl (Frontiers in Immunology, 2022)
African trypanosomes are extracellular flagellated unicellular protozoan parasites transmitted by tsetse flies and causing Sleeping Sickness disease in humans and Nagana disease in cattle and other livestock. These diseases are usually characterized by the development of a fatal chronic inflammatory disease if left untreated. During African trypanosome infection and many other infectious diseases, the immune response is mediating a see-saw balance between effective/protective immunity and excessive infection-induced inflammation that can cause collateral tissue damage. African trypanosomes are known to trigger a strong type I pro-inflammatory response, which contributes to peak parasitaemia control, but this can culminate into the development of immunopathologies, such as anaemia and liver injury, if not tightly controlled. In this context, the macrophage migration inhibitory factor (MIF) and the interleukin-10 (IL-10) cytokines may operate as a molecular “Yin-Yang” in the modulation of the host immune microenvironment during African trypanosome infection, and possibly other infectious diseases. MIF is a pleiotropic pro-inflammatory cytokine and critical upstream mediator of immune and inflammatory responses, associated with exaggerated inflammation and immunopathology. For example, it plays a crucial role in the pro-inflammatory response against African trypanosomes and other pathogens, thereby promoting the development of immunopathologies. On the other hand, IL-10 is an anti-inflammatory cytokine, acting as a master regulator of inflammation during both African trypanosomiasis and other diseases. IL-10 is crucial to counteract the strong MIF-induced pro-inflammatory response, leading to pathology control. Hence, novel strategies capable of blocking MIF and/or promoting IL-10 receptor signaling pathways, could potentially be used as therapy to counteract immunopathology development during African trypanosome infection, as well as during other infectious conditions. Together, this review aims at summarizing the current knowledge on the opposite immunopathological molecular “Yin-Yang” switch roles of MIF and IL-10 in the modulation of the host immune microenvironment during infection, and more particularly during African trypanosomiasis as a paradigm.